Temperature-Dependcnt Growth of InP By Plasma-Enhanced GSMBE - Mitchell, Bruce Daniel (My University, 1995)
This thesis reports on study of the effects of various plasmas on the growth of InP films by GSMBE. The samples were grown at temperatures ranging from 232 to 500°C. The plasmas were generated by electron cyclotron resonance, giving a broad distribution of ion energies in the 10-50 cV range. H. D, He and Ar plasmas were studied. Films were also grown at the same temperatures without plasma, as references.
The samples were characterized by: Nomarski phase contrast microscopy, Xray double crystal diffraction, Hall effect measurements, photoluminescence (PL), variable-energy positron annihilation, thermal desorption, nuclear reaction analysis and capacitance/voltage profiling. The Xray, Hall and PL measurements were repeated after the samples were annealed at 730°C for 10 seconds. In no case was the material produced of comparable quality to that grown under standard conditions (465°C, no plasma).
The films grown without plasma were n-type, reaching a carrier concentration of approximately 2x10¹⁸/cm³ at 300°C. This is in agreement with published results, which showed that the donor defect responsible is a P atom on an In site. This defect occurred in sufficiently high concentrations to mask the effects of the plasmas below 400°C.
H plasma increased the carrier concentration by approximately 7x10¹⁶/cm³. Some H atoms appear to bond to P atoms in the crystal, resulting in an excess In electron. The carrier concentration was not affected by annealing. Additional H atoms may be present as interstitials, causing a reduction in mobility and a broad PL peak near 1.05 eV. These effects were removed by annealing.
D plasma produced similar effects to H plasma, but the carrier concentration and mobility were lower. P interstitials, which act as deep acceptors, may be produced by recoiling surface P atoms into the bulk. Beryllium dopant, at a concentration of 2x10¹⁸/cm³), was passivated by this plasma. Silicon dopant was not strongly affected.
He plasma produced P interstitials and P vacancies, by recoil displacement from the surface and in the bulk. More P interstitials were produced, compensating up to 10¹⁷/cm³ carriers. The interstitials were more mobile, diffusing out during the 500°C growth and during annealing.
The effects of the Ar plasma were small enough to be masked by the weak H plasma that results from H backstreaming.
Films grown at 400°C or less without plasma had textured surfaces. The plasmas usuaIly smoothed the surfaces at these temperatures, resulting in defect densities lower even than occured at 465°C without plasma. Above 400°C. none of the plasmas significantly affected the surface defect densities.
Keywords: Engineering Physics; Engineering Physics